Urothelial carcinoma; an overview of histology, molecular subtypes, and clinical implications based on the latest WHO classification - Fateme Khalatbari; Miremad Moafi-Madani; Ali Amin (Journal of Nephropathology, 2023)
The incidence of urothelial carcinoma is increasing worldwide (including in Iran). Bladder cancer can be classified in various manners according to the standardized histomorphology set by the World Health Organization (WHO). Various genetic modifications occurring at the DNA level and the resulting variations in RNA expression give rise to different subcategories that have important implications for diagnosis, prognosis, and treatment. The molecular basis of these morphologic variances is now better understood because of recent developments in molecular biology. With updates on the genetic and clinical characteristics, we highlight the histologic traits of the divergent differentiation and subtypes recognized by the most recent WHO classification (5th edition). Molecular subtypes of lower and upper tract cancer can be used to characterize their clinical behaviors and determine therapeutic responses to neoadjuvant chemotherapy. In this overview article, we also present a preliminary analysis of our ongoing data collection on molecular features of urothelial carcinoma.